2017
DOI: 10.18632/oncotarget.17912
|View full text |Cite
|
Sign up to set email alerts
|

The nucleocapsid proteins of mouse hepatitis virus and severe acute respiratory syndrome coronavirus share the same IFN-β antagonizing mechanism: attenuation of PACT-mediated RIG-I/MDA5 activation

Abstract: Coronaviruses (CoVs) are a huge threat to both humans and animals and have evolved elaborate mechanisms to antagonize interferons (IFNs). Nucleocapsid (N) protein is the most abundant viral protein in CoV-infected cells, and has been identified as an innate immunity antagonist in several CoVs, including mouse hepatitis virus (MHV) and severe acute respiratory syndrome (SARS)-CoV. However, the underlying molecular mechanism(s) remain unclear. In this study, we found that MHV N protein inhibited Sendai virus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 85 publications
1
69
0
Order By: Relevance
“…RIG-I is also the aim for many coronaviruses. The nucleocapsid proteins of MHV and SARS-CoV antagonist IFN-β by attenuation of PACT-mediated RIG-I activation (Ding et al, 2017). The accessory protein NS6 encoded by PDCoV antagonized IFN-β production by interfering with the binding of RIG-I to double-stranded RNA .…”
Section: Discussionmentioning
confidence: 99%
“…RIG-I is also the aim for many coronaviruses. The nucleocapsid proteins of MHV and SARS-CoV antagonist IFN-β by attenuation of PACT-mediated RIG-I activation (Ding et al, 2017). The accessory protein NS6 encoded by PDCoV antagonized IFN-β production by interfering with the binding of RIG-I to double-stranded RNA .…”
Section: Discussionmentioning
confidence: 99%
“…In an RNP reconstitution assay, knocking down PACT in IAV-infected A549 cells enhanced vRNA production and the subsequent IFN response 59 . Of interest, there might be interplay between PACT and other viral molecules, such as the herpes simplex virus type 1 (HSV-1) Us11 protein, Middle East respiratory syndrome coronavirus (MERS-CoV) 4a and the nucleocapsid of the Ebola virus (EBOV) VP35, mouse hepatitis virus (MHV) N proteins and influenza A virus NS1 [60][61][62][63] . Hence, PACT might be a common target to counteract innate immunity response induced by different viruses with the potential to be developed into a new broad-spectrum antiviral drug.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of inhibition of type I IFN response by IFNβ has been closely investigated in several viruses. For example, in TGEV, PEDV, murine hepatitis virus, severe acute respiratory syndrome (SARS)-CoV, and middle east respiratory syndrome (MERS)-CoV, it has been reported that structural proteins, excluding non-structural proteins and spike protein, inhibit IFNβ production (Case et al, 2018(Case et al, , 2016Ding et al, 2017;Hu et al, 2017;Li et al, 2016;Lu et al, 2011;Lui et al, 2016;Zhang et al, 2016). However, it is unclear whether type I IFN responses are inhibited by FCoV.…”
Section: Introductionmentioning
confidence: 99%